Epidemiological evaluation of rubella virus infection among pregnant women in Ibadan, Nigeria (2015)
Rubella is a vaccine-preventable, mild rash-inducing viral disease with complications that include a spectrum of birth defects in the developing fetus, especially if the infection is acquired in the early months of pregnancy. Consequently, the primary objective of global rubella control programs is prevention of congenital rubella infection and associated birth defects. Despite the availability of safe and effective vaccines, and the elimination of the rubella virus in many developed countries, substantial commitment to rubella control has not been demonstrated in developing countries. This study appraises immunity to rubella, and consequently makes appropriate recommendations aimed at facilitating effective control. A cross-sectional sero-surveillance study was carried out among defined 272 consenting ante-natal clinic attendees in south-western, Nigeria. Prevalence rates of 91.54% and 1.84% were recorded for the anti–rubella virus (anti-RV) IgG and IgM, respectively. Also, 90.7% and 92.3% of the women aged ≤30 years and >30 years, respectively, had detectable anti-RV IgG. No significant association (p = 0.94) was recorded between anti-RV IgG detection and age of the women. Previous exposure and susceptibility of significant fraction of the population to rubella infection were confirmed. Considerable political commitment and promotion of free rubella immunization specifically for women with childbearing potential were recommended.